2009
DOI: 10.1021/ja808649g
|View full text |Cite
|
Sign up to set email alerts
|

Spin Dynamics in the Negatively Charged Terbium (III) Bis-phthalocyaninato Complex

Abstract: The experimental and theoretical study of the electron spin dynamics in the anionic form of a single-ion molecule magnet (SIMM), the bis-phthalocyaninato terbium (III) molecule [Pc(2)Tb](-)[TBA](+), has been addressed by means of solid state (1)H NMR spectroscopy. The magnetic properties of the caged Tb(3+) metal center were investigated in a series of diamagnetically diluted preparations, where the excess of tetrabutylamonium bromide ([TBA]Br)(n) salt was used as diamagnetic matrix complement. We found that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
123
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(130 citation statements)
references
References 65 publications
7
123
0
Order By: Relevance
“…All reagents were purchased from Across or Aldrich and used without further purification. A mixture of 1,2-dicyanobenzene (42 mmol), Y(acac) 3 ·4H 2 O (5 mmol), and 1,8-diazabicyclo [5,4,0]undec-7-ene (DBU) (21 mmol) in 50 mL of 1-pentanol was refluxed for 1.5 days. The solution was allowed to cool to room temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All reagents were purchased from Across or Aldrich and used without further purification. A mixture of 1,2-dicyanobenzene (42 mmol), Y(acac) 3 ·4H 2 O (5 mmol), and 1,8-diazabicyclo [5,4,0]undec-7-ene (DBU) (21 mmol) in 50 mL of 1-pentanol was refluxed for 1.5 days. The solution was allowed to cool to room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Pc-based compounds have attracted significant interest in the last decade after it has been suggested that high temperature superconductivity could be induced in these materials by alkali doping 3 and, more recently, when it has been recognized that neutral [LnPc 2 ] 0 molecules, with Ln a lanthanide ion, are molecular nanomagnets with extremely long coherence times at liquid nitrogen temperature. [4][5][6][7][8] Owing to the flat shape of Pc molecules, the structure of Pc-based materials is typically characterized by chains along which Pc molecules tend to stack. 9 Accordingly some of the Pc-based materials show many similarities to the Beechgaard salts.…”
Section: Introductionmentioning
confidence: 99%
“…Further progress in the field requires a detailed understanding of structural properties and magnetic interactions of an individual SMM in contact with a ferromagnetic electrode in an atomically well-defined environment. We select bis(phthalo cyaninato)terbium(III) (TbPc 2 ) as a model-type system because of its high blocking temperature (T B~3 0-50 K) 11,12 , its comparably small size and its high stability that allows for thermal deposition in ultrahigh vacuum environments.…”
mentioning
confidence: 99%
“…Doping a small amount of the paramagnetic ion into a diamagnetic host lattice (e.g., the Y III isostructure molecules) often results in reduced QTM. 35 The effects of intramolecular ff interaction on the rate of QTM are complicated. 36 In heteroleptic triple-decker [(Pc)Tb(Pc)-Tb(Pc (29) with an octabutoxyphthalocyanate and two unsubstituted phthalocyanates, the lanthanide ions exist along the fourfold symmetry axis with a separation of ca.…”
Section: Dipole-dipole Interactions For Reducing Qtmmentioning
confidence: 99%